TOLD LIKE IT IS! AN EVALUATION OF AN INTEGRATED ORAL DEVELOPMENT PILOT PROJECT - David Barr; Jonathan Leakey; Alexandre Ranchoux (Language Learning and Technology)
Much established pedagogical and CALL (computer-assisted language learning) research advocates an integrated constructivist approach to the use of technology in language learning. This paper reports on a pilot project delivered to first year undergraduate French students. The project aim was to deliver a blend of collaborative and individual learning through a combination of CALL programs and online activities alongside traditional face-to-face conversation classes. Using quantitative analysis of a pre- and posttest and a variety of questionnaires, this project assessed student progress in developing oral skills across two groups, one (the treatment group) using technology and the other (the comparison group) being a traditional conversation class. Each group covered the same content and underwent the same assessment procedures. In addition, through qualitative analysis measures, the project evaluated the role played by additional variables in the learning process, as well as student and staff reactions to the two approaches. The study concludes by showing that while progress was made by both groups, the progress made by those not using technology was significantly greater than that made by students using technology over a short-term study. It also highlights the need for developing pedagogy to ensure that CALL-based teaching goes beyond rehearsal activity to achieve message-orientated communication.